Inter-sectoral relations to accelerate the formation of technological innovation systems: determinants of actors’ entry into marine renewable energy technologies - Bento, N. (2021)
Decarbonizing the energy system requires new technologies, whose formation and diffusion needs the attraction of actors from different sectors to compose the value chain. Sectoral interactions are crucial and dependent on contextual and technological factors, as well as firm-specific characteristics. This paper examines the determinants of firm diversification towards a new technology and their role in sectoral interactions. We combine concepts from technological innovation systems (TIS), sectoral innovation systems and organization studies to examine the drivers of actors' entry as well as their impact on systems’ formation, through the effect on inter-sectoral relations associated with technological variety and relatedness. The development and demonstration of marine renewable energy technologies (MRET) in Portugal over the past two decades provides the empirical case. A database of 237 companies includes responses from a survey of a large part of the actors involved in MRET and potential entrants. A standard binary logit model estimates the effect of a set of drivers of firms' entry in MRET. Firms are more driven by variety-led factors and technology maturity, than by their technological capacity and sectoral proximity. We derive implications for policy and theory, namely for the conceptualization of inter-sectoral relations in TIS.